PENGEMBANGAN APLIKASI WISTLE BLOWING SYSTEM (WBS) PPNP DENGAN AGILE METHOD - Khomarudin, Agus Nur; Amrizal, Amrizal; Novita, Rina; Aulia, Romy (Smart Education, 2025)
Abstract: The effective implementation of a Whistleblowing System (WBS) reflects an organizations commitment to the principles of good governance and compliance with applicable laws and regulations. In order to realize good governance at Politeknik Pertanian Negeri Payakumbuh (PPNP), various efforts are required to overcome barriers that may hinder the achievement of the institutions vision. One such barrier may take the form of violations. Therefore, any potential violations within the PPNP environment need to be prevented and identified at an early stage. As a preventive and early detection measure against misconduct, PPNP needs to implement a Whistleblowing System as a reporting medium for violations committed by members of the academic community. This study aims to develop a WBS application that can be used as a reporting platform for violations within the PPNP environment. The research adopts stages from the Agile Method, which include the following phases: Plan, Design, Develop, Test, Deploy, Review, and Launch. In general, this study has produced a product in the form of a WBS system for PPNP, which has been tested for both validity and effectiveness. The validity test of the product yielded a score of 0.90, categorized as Valid, while the effectiveness test produced a score of 0.91, classified as High-g or highly effective. Based on these test results, it can be concluded that the WBS developed in this study is feasible and can be implemented at Politeknik Pertanian Negeri Payakumbuh as a means to support the realization of good governance within the institution.Keyword: Whistleblowing System; Good Governance; Agile Method.Abstrak: Implementasi Whistleblowing System (WBS) secara efektif mencerminkan komitmen organisasi terhadap prinsip good governance dan kepatuhan terhadap peraturan perundang-undangan yang berlaku. Dalam rangka mewujudkan tata kelola yang baik di Politeknik Pertanian Negeri Payakumbuh, diperlukan berbagai upaya untuk mengatasi hambatan yang dapat menghalangi pencapaian visi institusi. Salah satu hambatan tersebut dapat berupa terjadinya pelanggaran. Oleh karena itu, pelanggaran yang mungkin terjadi di lingkungan Politeknik Pertanian Negeri Payakumbuh perlu dicegah dan diidentifikasi sejak dini. Sebagai langkah preventif dan deteksi awal terhadap pelanggaran, Politeknik Pertanian Negeri Payakumbuh perlu mengimplementasikan sistem Whistleblowing sebagai media pelaporan pelanggaran yang dilakukan oleh warga kampus. Penelitian ini bertujuan untuk menghasilkan aplikasi wbs yang dapat digunakan sebagai media pelaporan pelanggaran atau Whistleblowing System (WBS) di lingkungan Politeknik Pertanian Negeri Payakumbuh. Penelitian ini menggunakan tahapan yang diadopsi dari tahapan pada Agile Method, yang terdiri dari tahap: Plan, Design, Develop, Test, Deploy, Review dan Launch. Secara umum penelitian ini telah menghasilkan sebuah produk yaitu sistem WBS pada PPNPdan telah diuji meliputi uji validitas dan efektifitas. Hasil uji validitas produk memperoleh nilai 0,90 dengan kategori Valid dan Uji efektifitas memperoleh nilai 0,91 dengan kriteria High-g atau efektifitas tinggi. Berdasarkan hasil uji produk maka dapat disimpulkan bahwa sistem WBS dalam penelitian ini layak dan dapat diterapkan pada kampus PPNP dalam rangka mewujudkan tata kelola yang baik di Politeknik Pertanian Negeri Payakumbuh.Kata kunci: Whistleblowing System; Good Governance; Agile Method.